Existence of Renormalized Solution of Some Elliptic Problems in Orlicz Spaces - Aharouch, Lahsen; Bennouna, Jaouad; Touzani, Abdelfettah (Revista Matemática Complutense, 2009)
In this paper, we study the problem:—div a(x, u, ∆u) — div Φ(u) + g(x; u) = f in the framework of Orlicz spaces. The main contribution of our work is to prove the existence of a renormalized solution without any restriction on the N-function of the Orlicz space.